Pengaruh Penggantian Pupuk Anorganik dengan Pupuk Kandang terhadap Pertumbuhan, Produksi dan Daya Simpan pada Umbi Bawang Merah - Romdoni, Arif; Suwarto, Suwarto; Maharijaya, Awang; Yuliani, Titiek (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
Excessive use of inorganic fertilizers is suspected to be the cause of low productivity and poor bulb storability that reduced their use. Goat manure organic fertilizer (GMOF) can be an alternative in reducing the use of these inorganic fertilizers. The study was conducted in March to June 2019 in the shallot field at Sukorejo Village, Rejoso District, Nganjuk Regency, East Java. The research aims to determine the dose of inorganic fertilizer which can be reduced by adding goat manure to increase the growth and production of shallot bulbs. This experiment used 2 factors, namely manure consisting of 2 levels (0 and 10 tons ha-1) and inorganic fertilizer consisting of 5 levels (0, 25, 50, 75, and 100% inorganic fertilizer reference dose). The treatment was repeated 4 times so that there were 40 experimental plots with a size of 2 m x 4 m, using Super Philip variety. The addition of 10 tons ha-1 of GMOF to shallot cultivation in Nganjuk Regency could reduce the use of inorganic fertilizer to 50%. Keywords: goat manure, nutrient uptake, organic, Super Philip